2019
DOI: 10.3390/molecules24061092
|View full text |Cite
|
Sign up to set email alerts
|

Biological Evaluation and Molecular Dynamics Simulation of Chalcone Derivatives as Epidermal Growth Factor-Tyrosine Kinase Inhibitors

Abstract: Targeted cancer therapy has become a high potential cancer treatment. Epidermal growth factor receptor (EGFR), which plays an important role in cell signaling, enhanced cell survival and proliferation, has been suggested as molecular target for the development of novel cancer therapeutics. In this study, a series of chalcone derivatives was screened by in vitro cytotoxicity against the wild type (A431 and A549) and mutant EGFR (H1975 and H1650) cancer cell lines, and, subsequently, tested for EGFR-tyrosine kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…As shown in Figure 4 B, the IC 50 against EGFR-TK of VF16 is 7.85 ± 0.88 nM, which is significantly lower than the erlotinib (IC 50 of 26.09 ± 5.42 nM). Additionally, the inhibitory activity of VF16 is greater than that of the chalcones that have been previously reported to inhibit EGFR activity (IC 50 ranked from 10.3 to 15.4 µM) [ 25 ].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As shown in Figure 4 B, the IC 50 against EGFR-TK of VF16 is 7.85 ± 0.88 nM, which is significantly lower than the erlotinib (IC 50 of 26.09 ± 5.42 nM). Additionally, the inhibitory activity of VF16 is greater than that of the chalcones that have been previously reported to inhibit EGFR activity (IC 50 ranked from 10.3 to 15.4 µM) [ 25 ].…”
Section: Resultsmentioning
confidence: 98%
“…Vinyl sulfone (VF) is an organic compound, where its core structure is similar to that of chalcones [ 21 , 22 , 23 , 24 ] ( Figure 1 ). Previous study has shown that chalcone derivatives can inhibit EGFR activity with the IC 50 value ranged from 10.3–15.4 µM [ 25 ]. Thus, we hypothesized that VF derivatives can inhibit EGFR-TK activity in a manner similar to chalcones.…”
Section: Introductionmentioning
confidence: 99%
“…35 Furthermore, the equilibrium constant Ki of interaction between erlotinib and EGFR with 19Del mutation is far lower than that of EGFR with L858R mutation. 36 Wang et al revealed that EGFR protein with 19Del mutation exhibits lower degradation rate than EGFR protein with L858R mutation because of lower interaction with c-Cbl. 37 Second, from a clinical point of view, in a randomized controlled phase III clinical trial (EURTAC study) 16 that compared first-line EGFR TKI treatment with chemotherapy in advanced NSCLC, patients with different EGFR mutation types had different benefit extents from EGFR TKI.…”
Section: Discussionmentioning
confidence: 99%
“…has shown that the autophosphorylation site of EGFR with L858R mutation is different from that with 19Del mutation, and the tyrosine residues of the 845 code in EGFR with L858R mutation is highly phosphorylated which results in different downstream signaling pathways 35 . Furthermore, the equilibrium constant Ki of interaction between erlotinib and EGFR with 19Del mutation is far lower than that of EGFR with L858R mutation 36 . Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Chalcones have attracted considerable attention because of their promising therapeutic effects. Natural and synthetic chalcones have demonstrated a broad spectrum of therapeutic effects including antibacterial, antifungal, antiviral, anti‐inflammatory, antioxidant, and most importantly, anticancer activities (Sangpheak et al., 2019). According to Mphahlele, Maluleka, Parbhoo, and Malindisa (2018), chalcone‐based compounds have several mechanisms of action, among which are induction of apoptosis, DNA and mitochondrial damage, inhibition of angiogenesis and kinase inhibition.…”
Section: Introductionmentioning
confidence: 99%